Qualitative research as theater: fieldwork in a South African township through the prism of Goffman’s dramaturgical metaphor - Masquillier, Caroline (Afrika Focus, 2016)
This autoethnographic paper reflects on the qualitative fieldwork I conducted in a township on the outskirts of Cape Town, South Africa. By exploring how a metaphor can assist in autoethnographic reflection, I aim to gain insight into how data can best be collected in deprived informal settlements characterized by high crime rates. This autoethnographic paper draws on the autobiographical materials of the researcher as primary data. This self-reflexive route, which relied on Erving Goffman’s dramaturgical metaphor, helped me to process my various fieldwork experiences in a more systematic manner. Attempting to reconcile my ‘work’ role – a professional, reliable and con dential advisor – with my ‘non-work’ role – my supposed real self – involved emotion management and the tools of the stage outlined by Goffman in order that the fieldwork could be conducted in an atmosphere of trust while maintaining a professional distance. Key words: autoethnography, metaphor, role, social interaction, Erving Goffman, participant observation, in-depth interview, South Africa